Role of Extracellular Vesicles as Potential Diagnostic and/or Therapeutic Biomarkers in Chronic Cardiovascular Diseases - Martin-Ventura, Jose Luis; Roncal, Carmen; Orbe, Josune; Blanco-Colio, Luis Miguel (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular diseases (CVDs) are the first cause of death worldwide. In recent years, there has been great interest in the analysis of extracellular vesicles (EVs), including exosomes and microparticles, as potential mediators of biological communication between circulating cells/plasma and cells of the vasculature. Besides their activity as biological effectors, EVs have been also investigated as circulating/systemic biomarkers in different acute and chronic CVDs. In this review, the role of EVs as potential diagnostic and prognostic biomarkers in chronic vascular diseases, including atherosclerosis (mainly, peripheral arterial disease) and abdominal aortic aneurysms, will be described. Mechanistically, we will analyze the implication of EVs in pathological processes associated to chronic vascular remodeling, with special emphasis in their role in vascular calcification. Specifically, we will focus on the participation of EVs in calcium accumulation in the pathological vascular wall, involving the phenotypic change of vascular smooth muscle cells to osteoblast-like cells. The knowledge of the implication of EVs in the pathogenic mechanisms of vascular wall remodeling is still to be completely deciphered but there are promising results supporting their potential translational application to the diagnosis and therapy of different CVDs.